The Role of Women in Livelihood Perspective of Contemporary Mufassirs - Zainab Rahmatulloh Hikmatul Haq; Moh. Aceng Hakkinnazili M; Ari Kurnia Efendi (MUWAZAH : jurnal kajian gender, 2023)
The purpose of this study is to describe problems related to livelihood according to the perspective of Contemporary Mufassir. Scholars agree that a living is borne by the husband in meeting household needs, but in the contemporary era it is often found that women work outside the home as the main support for breadwinners in meeting household needs. Some say that it is natural for women to stay at home, but we often encounter the phenomenon of women as breadwinners outside the home. The author wants to examine the issue of subsistence from the perspective of Contemporary Mufassir, Sheikh Mutawalli Sya'rowi, M. Quraish Shihab and Buya Hamka. The writing method uses descriptive qualitative research with the type of Library Research. The primary source comes from the book of Tafsir As-Sya'rawi, Tafsir Al-Mishbah, Tafsir Al-Azhar. Data collection techniques from documentation with qualitative content analysis as the analysis technique. The results of the research in general show that the three mufassirs allow women to work for a living. As-Sya'rawi and Quraish Shihab both clearly stated the permissibility of working for women. As for Buya Hamka, he allowed it, but he seemed to emphasize more on women to stay at home.